Ice hockey elite: post-retirement psychosocial health analysis - Rodygina, Yu. K.; Potapchuk, A. A.; Matveev, S. V. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to test and analyze the post-retirement psychosocial health of the national elite ice hockey players and offer recommendations on how their social health disorders and early passing away could be prevented.